Experience of the postpartum breastfeeding mothers regarding the breastfeeding practice - Aline Nogueira Santos; Valdecyr Herdy Alves; Gleiciana Sant' Anna Vargas; Diego Pereira Rodrigues; Rosangela de Mattos Pereira de Souza; Giovanna Rosário Soanno Marchiori (Universidade Federal de Santa Maria, 2016)
Aim: To understand the practice of breastfeeding mothers regarding the breastfeeding process under the context of the guidance received at the Family Health Strategy (FHS) of the municipality of Silva Jardim. Method: descriptive exploratory study, with a qualitative approach, through semi-structured interviews with twenty-one breastfeeding mothers assigned to the FHS area of Silva Jardim. Data collection occurred from January to April 2014. Results: two categories emerged: difficulties of breastfeeding from the viewpoint of the breastfeeding mothers: the need of implementing a line of care on breastfeeding in FHS; Promotion and support to breastfeeding during postpartum: a challenge for FHS. Conclusion: in this study, the experience of breastfeeding mothers in the breastfeeding process is related to the lack of cohesive information, allowing the adoption of inappropriate practices.